Fresno County Bar Association Bar Banquet at Elks Lodge - Watkins, Howard::::::::: (1983)
In-coming Fresno County Bar Association President Rodney Worrel 3-dimensional map of California as thank you gift to out-going Fresno County Bar Association President Doug Jensen